Organización efectiva para la implementación de sistemas ERP en el área de manufactura de una empresa PYME (2012)
The purpose of the article is to show in a descriptive way the organization, resources and sequence management of the different planning process in the manufacturing enterprise and how to implement all this in the information system ERP (Enterprise Resource Planning) to improve and control all the planning, scheduling and execution in the manufacturing system. Also contributes to increase the efficiency and make more competitive the enterprise through the cost reduction and better quality. The article is maked in five steps that shall be involve in sequential order: 1-forecasting and/or demand, 2-delivery resource planning DRP, 3-master planning schedule MPS, 4-material requirement planning MRP and 5- capacity requirement planning CRP.